GREEN SYNTHESIS OF 3, 4-DIHYDROPYRIMIDINONE USING FERROUS SULPHATE AS RECYCLABLE CATALYST. - Gurumeet C. Wadhawa, Dinanath D. Patil (Journal of Pharmaceutical Research and Opinion, 2014)
The Biginelli one-pot three-component cyclocondensation was applied in this work to prepare 3,4-dihydropyrimidinone and its analogues are synthesized by A simple, green and efficient solventless procedure for the, ferros sulphate as a recycling catalyst, from a Diversity of aromatic aldehydes, _-ketoesters and urea under solvent free condition and using green route .this method have several advantages such as short reaction time ,easy experimental and work up.,with high yield.